2022
DOI: 10.3389/fphy.2022.1006451
|View full text |Cite
|
Sign up to set email alerts
|

Vlasov simulation of the emissive plasma sheath with energy-dependent secondary emission coefficient and improved modeling for dielectric charging effects

Abstract: A one-dimensional Vlasov–Poisson simulation code is employed to investigate the plasma sheath considering electron-induced secondary electron emission (SEE) and backscattering. The SEE coefficient is commonly treated as constant in a range of plasma simulations; here, an improved SEE model of a charged dielectric wall is constructed, which includes the wall charging effect on the SEE coefficient and the energy dependency of the SEE coefficient. Pertinent algorithms to implement the previously mentioned SEE mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Sub-surface charge migration is regulated by the trap states, which affects the above-surface process of flashover development, including SEEA, surface charging, and outgassing, and ultimately determines the surface insulation. On the one hand, the trap density and energy levels could affect the SEY by changing the trapping escape mean free path and probability of the internal SEs excited by the incident electrons (Figure d). , It has been demonstrated that the increase in trap density always yields lower SEE for a positively charged dielectric surface, which is preferable for better surface insulation. Deep trap states mainly impede surface charge emission to alleviate the surface charging and hence increase flashover voltage, which is more pronounced with higher deep trap state density and the trap energy level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sub-surface charge migration is regulated by the trap states, which affects the above-surface process of flashover development, including SEEA, surface charging, and outgassing, and ultimately determines the surface insulation. On the one hand, the trap density and energy levels could affect the SEY by changing the trapping escape mean free path and probability of the internal SEs excited by the incident electrons (Figure d). , It has been demonstrated that the increase in trap density always yields lower SEE for a positively charged dielectric surface, which is preferable for better surface insulation. Deep trap states mainly impede surface charge emission to alleviate the surface charging and hence increase flashover voltage, which is more pronounced with higher deep trap state density and the trap energy level.…”
Section: Resultsmentioning
confidence: 99%
“…Deep trap states mainly impede surface charge emission to alleviate the surface charging and hence increase flashover voltage, which is more pronounced with higher deep trap state density and the trap energy level. The trapping mean free path of internal SEs, excited by the primary electrons, is proportional to ( n T σ T ) −1 with n T and σ T , the trap density and trapping cross-section . The deep trap energy level mainly acts on the trapping cross-section, but a quantitative relation remains elusive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one mechanism, the emission of electrons is suppressed by the increase in energy depth and density of deep surface traps. Said et al [173] first established a relation between the SEE current density and trap level [174], and then the model was developed by Sun and Zhang et al, they indicated the SEE yield significantly decreased with the trap cross section (level) and density. Since the traps capture carriers that migrate on the surface, the surface flashover voltage increases.…”
Section: Effects Of Surface Traps On Surface Flashovermentioning
confidence: 99%
“…To form the SEEA, SEE on the insulator is indispensable. The treatment of the SEE process here is different from the previously used averaged SEEY for all electrons in emissive sheath studies [55,64], instead a SEEY matrix δe of dimension dvx × dvy is constructed, with dvx and dvy the grid number in vx and vy direction. The matrix δe represents SEEY of each element (v x,i , v y,j ) in phase space.…”
Section: Model Setupmentioning
confidence: 99%